Diagnostic accuracy of the muscle-retracting sign for determining deep submucosal invasion in early rectal cancer: a prospective observational study - Argenziano, Maria Eva; Sorge, Andrea; Montori, Michele; Poortmans, Pieter Jan; Smeets, Sander; Tornai, Tamas; Hoorens, Anne; Debels, Lynn K.; Desomer, Lobke; Tate, David J. (Endoscopy, 2025)
This study aimed to determine the accuracy of the muscle-retracting sign (MRS) for the detection of deep submucosal invasion (SMI) in early rectal cancer.In this prospective observational single-center study, consecutive rectal lesions that underwent endoscopic resection using the pocket-detection method (PDM) between August 2023 and March 2025 were included. Directionality of the initial submucosal dissection targeted any morphologic or surface vascular pattern at risk of deep SMI to attempt MRS identification. Histopathology was the reference standard for MRS diagnostic accuracy in detecting deep SMI.38 rectal lesions (median size 30 mm [interquartile range 20]) were included. The PDM for detection of the MRS was successful in all cases, with MRS positivity in 15/38 cases (39.5%). Deep SMI was confirmed in 15/38 cases (39.5%). The accuracy of MRS positivity for deep SMI detection was 84.2% (95%CI 69.6%–92.6%), with a sensitivity of 80.0% (95%CI 54.8%–92.9%), specificity of 87.0% (95%CI 67.9%–95.5%), positive likelihood ratio of 6.13, negative likelihood ratio of 0.23, and area under the receiver operating characteristic curve of 0.83 (95%CI 0.71–0.96). The rate of R0 resection was 92.1% (35/38).The MRS detected using the PDM demonstrated moderate-to-high accuracy for the prediction of deep SMI in early rectal cancer. This finding may allow the precise selection of an endoscopic resection strategy based on invasion depth for the minimally invasive treatment of early rectal cancer.